Lithium ion battery and preparation method thereof
By applying functional coatings and surface coatings on the positive electrode and separator of the lithium-ion battery, the problem of thermal runaway in the overcharge state is solved, and the structural stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202411996431.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Lithium-ion batteries can easily lead to safety hazards such as thermal runaway, battery deformation, and liquid leakage under overcharge. The existing anti-overcharge measures are limited in effect.
The positive electrode containing a functional coating and a diaphragm including a surface coating are used, which consists of vinyl chloride-acrylate resin, aqueous acrylic resin and metal oxides. The surface coating of the diaphragm contains sodium fast ion conductors.
It improves the structural stability, circulation performance and overcharge resistance of lithium-ion batteries, reduces the risk of thermal runaway caused by overcharging, and improves the safety of the battery.
Smart Images

Figure CN119764530A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular, relates to a lithium ion battery and a preparation method thereof. Background Art
[0002] As the requirements for the energy density of lithium-ion batteries in pure electric vehicles, hybrid electric vehicles and portable energy storage devices continue to increase, people are looking forward to developing lithium-ion batteries with higher energy density and power density to achieve long-term endurance and energy storage of electric equipment.
[0003] However, when overcharged, lithium-ion batteries will not only generate a large amount of heat and gas, leading to increased internal pressure, deformation, and leakage, but also easily trigger side reactions in the battery, causing battery performance to deteriorate. On the one hand, under overcharge conditions, it is easy for excessive lithium elements to be embedded in the negative electrode, thereby growing lithium dendrites on the surface of the negative electrode, which can easily pierce the diaphragm and cause thermal runaway; on the other hand, under overcharge conditions, excessive lithium elements will escape from the positive electrode, which can easily cause the positive electrode structure to collapse, release a large amount of heat, and release oxygen, which will further accelerate the decomposition of the electrolyte. The internal pressure of the battery will experience an abnormal increase process. This loss of control of the internal pressure is a precursor to thermal runaway. Thermal runaway is a chain reaction. Once triggered, the heat inside the battery will accumulate rapidly, the temperature will rise sharply, and then cause irreversible changes in the structure of the electrode active material and the decomposition of the electrolyte, generating more heat, forming a vicious cycle. Eventually, it will cause safety hazards such as fire and explosion.
[0004] The main overcharge protection measures for lithium-ion batteries are as follows:
[0005] (1) By installing a current interruption device inside or outside the battery, such as installing a current interruption device (CID), an explosion-proof safety valve (Vent), and a PTC polymer switch in the battery's safety cap. However, before the overcharge protection device cuts off the battery current, the temperature inside the battery is already high. At this time, the diaphragm inside the battery usually shrinks, melts, collapses, etc., causing the positive and negative electrodes to directly contact and short-circuit, which in turn causes the battery temperature to rise sharply, triggering battery thermal runaway.
[0006] (2) By introducing anti-overcharge additives into the positive electrode and / or electrolyte, the anti-overcharge additives can preferentially decompose on the positive electrode surface to form a CEI film during battery cycling, which can protect the integrity of the electrode material to a certain extent and reduce the side reactions caused by the contact between the high-voltage positive electrode and the electrolyte. However, the anti-overcharge protective agent is not conducive to battery cycling and affects the battery life.
[0007] (3) Thermal shutdown isolation membranes and ceramic-coated isolation membranes are used inside the battery to improve the heat resistance of the battery. However, there are certain limitations, and the effect of improving the thermal runaway caused by the battery inside is not obvious.
[0008] (4) The purpose of improving overcharge safety is achieved by using a positive temperature coefficient (PTC) coating. However, the positive temperature coefficient coating has a slow response and the overcharge protection effect is limited. Summary of the invention
[0009] The object of the present invention is to provide a lithium ion battery and a preparation method thereof. The lithium ion battery adopts a positive electrode containing a functional coating and a diaphragm including a surface coating, thereby improving the structural stability and cycle performance of the lithium ion battery, and improving the flame retardant performance of the lithium ion battery in an overcharged state, thereby improving the overcharge resistance and safety of the lithium ion battery.
[0010] According to one aspect of the present invention, a lithium ion battery is provided, comprising a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode; the positive electrode comprises a positive electrode active coating, a functional coating and a current collector, the positive electrode active coating is connected to the current collector via the functional coating, the functional coating comprises vinyl chloride-acrylate resin, water-based acrylic resin and metal oxide, the metal oxide comprises at least one of aluminum oxide, zirconium oxide, zinc oxide, magnesium oxide and lithium oxide; the separator comprises a base film and a surface coating, the surface coating comprises a sodium fast ion conductor.
[0011] By setting functional coatings on both sides of the current collector of the positive electrode and setting a surface coating on the diaphragm, the overcharge resistance and flame retardancy of the battery can be improved under the premise of balancing the cycle performance of the battery. On the one hand, during the normal operation of the battery, by introducing vinyl chloride-acrylate resin and water-based acrylic resin as a binder in the functional coating of the positive electrode, not only the internal structure of the functional coating is improved, and it is not easy to fall off, crack, etc., but also it is conducive to the strong bonding between the functional coating and the current collector and the positive electrode active coating, thereby improving the structural stability of the positive electrode and reducing the impedance of the lithium-ion battery. The metal oxides in the functional coating are used to improve the conductivity and electrolyte permeability of the functional coating, and further reduce the impedance increase caused by the introduction of the functional coating into the positive electrode structure. At the same time, during the cycle of the battery, the surface coating containing sodium fast ion conductors in the diaphragm is used to improve the ionic conductivity of the diaphragm, effectively improving the rate performance and cycle performance of the battery.
[0012] On the other hand, when the battery is in an overcharged state, the functional coating of the positive electrode and the surface coating of the diaphragm can be used to improve the flame retardant properties of the battery and reduce the probability of thermal runaway of the battery due to overcharging. The use of a binder composed of vinyl chloride-acrylate resin and a water-based acrylic resin and a metal oxide can give the positive electrode self-extinguishing properties, and is beneficial to improving the thermal stability of the positive electrode. The functional coating is used to absorb the heat accumulated when the battery is overcharged, so that the overcharge coating forms the first anti-overcharge protection to prevent the battery from thermal runaway. At the same time, the surface coating of the diaphragm forms a second anti-overcharge protection. The sodium fast ion conductor in the surface coating of the diaphragm can react with the electrolyte during the formation of the battery cell to form a protective film. The protective film can block the crosstalk of combustible gases such as oxygen between the positive and negative electrodes to prevent thermal runaway of the battery.
[0013] In summary, by introducing the above-mentioned functional coating into the positive electrode and introducing the surface coating into the separator, the lithium-ion battery has excellent overcharge resistance and flame retardant properties while maintaining good structural stability and cycle stability, thereby improving the safety performance of the battery device, which is reflected in the fact that the battery device can withstand an improved ability to withstand a voltage exceeding its normal upper charging limit during the charging process, can tolerate overcharging during the charging process to a certain extent, and reduce safety risks caused by improper charging.
[0014] Preferably, the proportion of chlorine in the functional coating is 2.2 to 13.6 wt %. By adjusting the content of vinyl chloride-acrylate resin in the functional coating and the content of vinyl chloride monomer in the vinyl chloride-acrylate resin, the content of chlorine can be adjusted to the above range, thereby improving the flame retardant and self-extinguishing properties of the functional coating. When the battery is in an overcharged state, a large number of lithium ions escape from the positive electrode, causing the positive electrode structure to collapse and releasing a large amount of heat and gas. The chlorine element in the functional coating can be freed into the electrolyte, reducing the flammability of the electrolyte, while being conducive to forming a stable interface film at the positive electrode, inhibiting the interface side reactions caused by overcharging of the battery. When the battery causes thermal runaway due to overcharging, the internal temperature of the battery rises significantly. At this time, the chlorine element in the functional coating can capture the free radicals required for the combustion process, interrupt the chain propagation of the combustion reaction, and achieve a flame retardant effect.
[0015] Preferably, the mass ratio of the vinyl chloride-acrylate resin to the water-based acrylic resin is 5-30:5-30.
[0016] Preferably, in the raw materials used to prepare the functional coating, the proportion of vinyl chloride-acrylate resin is 5 to 30 wt %.
[0017] Preferably, in the raw materials used to prepare the functional coating, the proportion of the water-based acrylate resin is 5 to 30 wt %.
[0018] Preferably, in the raw materials used to prepare the functional coating, the metal oxide accounts for 2 to 40 wt %.
[0019] Preferably, in the raw materials for preparing vinyl chloride-acrylate resin, the content of vinyl chloride is 70 to 90 wt %.
[0020] Preferably, in the functional coating, the metal oxide includes metal oxide A and metal oxide B, metal oxide A includes at least one of aluminum oxide, zirconium oxide, zinc oxide, and magnesium oxide, and metal oxide B includes lithium oxide. The combination of metal oxide A and metal oxide B is beneficial to improving the structural stability and cycle stability of lithium-ion batteries, and also to improving the safety performance of lithium-ion batteries. Metal oxide A can broaden the upper limit of the heat that can be absorbed by the functional coating, and metal oxide B has good thermal stability and electrochemical stability. By using metal oxide A and metal oxide B at the same time, it is beneficial to balance the thermal stability and conductivity of the positive electrode, so that the lithium-ion battery can simultaneously exhibit excellent cycle capacity retention and overcharge resistance.
[0021] Preferably, the aluminum oxide includes at least one of boehmite (γ-Al2O3·H2O) and alumina.
[0022] Preferably, the zirconium oxide comprises zirconium oxide.
[0023] Preferably, the zinc oxide comprises zinc oxide.
[0024] Preferably, the magnesium oxide comprises magnesium oxide.
[0025] Preferably, the lithium oxide includes at least one of lithium iron phosphate (LiFePO 4 ), lithium iron manganese phosphate (LiMnFePO 4 ), and lithium manganese oxide (LiMn 2 O 4 ).
[0026] Preferably, in the functional coating, the mass ratio of metal oxide A to metal oxide B is 1-20:1-20.
[0027] Preferably, in the raw materials used to prepare the functional coating, the metal oxide A accounts for 1 to 20 wt %.
[0028] Preferably, in the raw materials for preparing the functional coating, the metal oxide B accounts for 1 to 20 wt %.
[0029] Preferably, in the functional coating, the mass ratio of metal oxide A to metal oxide B is 3-10:2-9.
[0030] Preferably, in the functional coating, the mass ratio of metal oxide A to metal oxide B is 6.5:5.5.
[0031] Preferably, in the positive electrode, the thickness of the functional coating is 1 to 5 μm. Adjusting the thickness of the functional coating to the above range can not only reduce the impedance of the lithium-ion battery to extend the cycle life of the battery device, but also improve the overcharge resistance and flame retardancy of the lithium-ion battery.
[0032] Preferably, the functional coating further includes a conductive agent, and the conductive agent includes at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, and graphene.
[0033] Preferably, in the raw materials used to prepare the functional coating, the conductive agent accounts for 0.1 to 3 wt %.
[0034] Preferably, the functional coating further comprises a dispersant, and the dispersant comprises at least one of sodium carboxymethyl cellulose (CMC), sodium sulfate salt, sodium sulfonate salt, and acrylate type polymer dispersant.
[0035] Preferably, in the raw materials used to prepare the functional coating, the dispersant accounts for 0.1 to 3 wt %.
[0036] Preferably, the positive electrode active coating layer includes polyvinylidene fluoride (PVDF).
[0037] Preferably, the positive electrode active coating includes lithium cobalt oxide.
[0038] Preferably, in the diaphragm, the surface coating also includes boron compounds and / or phosphorus compounds. On the one hand, during the normal operation of the battery, the sodium fast ion conductor, boron compound, phosphorus compound and other inorganic materials in the surface coating can provide support for the base membrane, effectively slow down the thermal shrinkage of the base membrane, and improve the structural stability of the base membrane during the battery cycle, and effectively prevent the lithium battery device from short-circuiting the positive and negative electrodes due to the shrinkage of the diaphragm during normal operation. On the other hand, when the lithium-ion battery is in an overcharged state, the boron compound and / or phosphorus compound in the surface coating undergoes thermal decomposition under the overcharge voltage, releasing crystal water, which plays the role of heat absorption cooling and diluting oxygen, thereby reducing the probability of thermal runaway due to overcharging.
[0039] Preferably, in the separator, the surface coating further comprises zinc borate.
[0040] Preferably, in the raw materials used to prepare the surface coating, the sum of the mass of the boron compound and the phosphorus compound accounts for 1 to 10 wt %. By adjusting the amount of the boron compound and the phosphorus compound added to the surface coating, thermal runaway caused by overcharging can be prevented, and the influence of the thermal decomposition products of the boron compound and the phosphorus compound on the battery cycle performance can be reduced.
[0041] Preferably, the surface coating further comprises polyvinylidene fluoride (PVDF).
[0042] Preferably, in the raw materials used to prepare the surface coating, the proportion of polyvinylidene fluoride (PVDF) is 3 to 20 wt %.
[0043] Preferably, the sodium fast ion conductor (NASCION type) includes at least one of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP).
[0044] Preferably, in the raw materials used to prepare the surface coating, the sodium fast ion conductor (NASCION type) accounts for 3 to 20 wt %.
[0045] Preferably, the thickness of the surface coating is 0.5 to 3 μm. Adjusting the thickness of the surface coating to the above range can, on the one hand, shorten the channel for ion migration, weaken polarization, and reduce the impedance of the lithium-ion battery, thereby extending the cycle life of the battery device and increasing the energy density of the lithium-ion battery; on the other hand, it can improve the mechanical strength and insulation effect of the diaphragm, so that the diaphragm can withstand various stresses to which the battery is subjected during assembly and use, prevent short circuits between the positive and negative electrodes, and at the same time enhance the thermal stability of the diaphragm and improve the overcharge resistance and flame retardant properties of the lithium-ion battery.
[0046] Preferably, in the diaphragm, both sides of the base film are respectively compounded with a layer of surface coating.
[0047] Preferably, the lithium-ion battery further comprises an electrolyte, and the lithium salt of the electrolyte comprises lithium hexafluorophosphate (LiFP6).
[0048] According to another aspect of the present invention, a method for preparing the above-mentioned lithium-ion battery is provided, comprising the following operations: a. preparing a positive electrode: applying a functional coating slurry for preparing a functional coating on both sides of a current collector, curing, and obtaining a composite layer containing a functional coating and a current collector, wherein the functional coating slurry comprises vinyl chloride-acrylate resin, aqueous acrylic resin, metal oxide, and solvent; then applying a positive electrode active slurry for preparing a positive electrode active coating on both sides of the composite layer, curing, and obtaining a positive electrode; b. preparing a diaphragm: applying a surface coating slurry for preparing a surface coating on both sides of a base film, curing, and obtaining a diaphragm.
[0049] Preferably, the solid content of the functional coating slurry is 10-15%.
[0050] Preferably, the method for preparing a lithium-ion battery further comprises an assembly operation: stacking the positive electrode, the separator, the negative electrode and the separator in sequence, and obtaining a battery cell through winding or lamination operation; and obtaining a lithium-ion battery through post-processing of the battery cell.
[0051] Preferably, the curing operation comprises baking.
[0052] Preferably, the post-processing includes at least one of packaging, baking, liquid injection, formation, secondary sealing, sorting, and testing the open circuit voltage of the battery.
[0053] Optionally, during the stacking process, the surface coating of the separator is oriented toward the positive electrode.
[0054] Optionally, during the stacking process, the surface coating of the separator is oriented toward the negative electrode.
[0055] Preferably, during the stacking process, the positive electrode active coating of the positive electrode faces the separator. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 A schematic diagram of the structure of the positive electrode in the lithium-ion battery provided by the present invention;
[0057] Figure 2 A schematic diagram of the structure of a separator in a lithium-ion battery provided by the present invention;
[0058] The corresponding relationship of the above-mentioned figure marks is: 1. first positive electrode active coating, 2. first functional coating, 3. current collector, 4. second functional coating, 5. second positive electrode active coating, 6. first surface coating, 7. base film, 8 second surface coating. DETAILED DESCRIPTION
[0059] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0060] Example 1
[0061] This embodiment provides a lithium-ion battery, including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0062] (1) Positive electrode
[0063] The structure of the positive electrode is Figure 1 As shown, it includes a first positive electrode active coating 1, a first functional coating 2, a current collector 3, a second functional coating 4, and a second positive electrode active coating 5, which are arranged in sequence. The first functional coating 2 and the second functional coating 4 are both functional coatings. The thickness of the first functional coating 2 is 3 μm, and the thickness of the second functional coating 4 is 3 μm. The current collector 3 is aluminum foil.
[0064] The composition of the raw materials used to prepare the functional coating of the positive electrode is shown in the following table:
[0065] Table 1. Raw material composition for preparing the functional coating of the positive electrode
[0066]
[0067] Among the raw materials for preparing the vinyl chloride-acrylate resin, the content of vinyl chloride monomer is 80%. Since the solvent in the functional coating slurry evaporates during the curing process, it is calculated that the content of chlorine element in the functional coating is 6.8wt%.
[0068] The method for preparing the positive electrode comprises the following operations:
[0069] S1. Prepare the raw materials according to the composition shown in Table 1, mix the components, and prepare a functional coating slurry with a solid content in the range of 10 to 15%. Use a sand grinder to sand the functional coating slurry, and then use a gravure coater to apply the functional coating slurry to both sides of the current collector 3. Curing, obtain a composite layer consisting of the functional coating and the current collector 3.
[0070] S2. Preparation of positive electrode:
[0071] A positive electrode active slurry for preparing a positive electrode active coating is prepared. The positive electrode active slurry includes polyvinylidene fluoride (PVDF), lithium cobalt oxide, and a conductive agent. The conductive agent includes conductive carbon black (SP) and carbon nanotubes (CNT). The positive electrode active slurry is coated on both sides of the composite layer, and after baking and rolling, a positive electrode is obtained.
[0072] Among them, in the positive electrode active coating, the content of lithium cobalt oxide is 97.6wt%, the content of polyvinylidene fluoride (PVDF) is 1wt%, the content of the conductive agent is 1.4wt%, and the mass ratio of conductive carbon black (SP) to carbon nanotubes (CNT) is 1:1.
[0073] (2) Negative electrode
[0074] The method for preparing the negative electrode comprises the following operations:
[0075] A negative electrode active slurry for preparing a negative electrode active coating is prepared. The negative electrode active slurry includes graphite, conductive carbon black (SP), styrene-butadiene rubber (SBR), and dispersant sodium carboxymethyl cellulose (CMC). The negative electrode active slurry is coated on the surface of a negative electrode current collector (carbon-coated copper foil), and after baking and rolling, a negative electrode is obtained.
[0076] Among them, in the negative electrode active coating, the content of graphite is 96wt%, the content of conductive carbon black (SP) is 1.3wt%, the content of styrene-butadiene rubber (SBR) is 1.5wt%, and the content of dispersant sodium carboxymethyl cellulose (CMC) is 1.2wt%.
[0077] (3) Diaphragm
[0078] The structure of the diaphragm is Figure 2 As shown, it includes a first surface coating 6, a base film 7 and a second surface coating 8 arranged in sequence. The first surface coating 6 and the second surface coating 8 are both surface coatings, the base film 7 is a commercially available heat-resistant ceramic diaphragm, the thickness of the first surface coating 6 is 1 μm, and the thickness of the second surface coating 8 is 1 μm.
[0079] The composition of the raw materials used to prepare the surface coating of the diaphragm is shown in the following table:
[0080] Table 2. Raw material composition for preparing the surface coating of the separator
[0081]
[0082] The method for preparing the separator comprises the following operations:
[0083] Prepare the raw materials according to the composition shown in Table 2, mix the components, and prepare a surface coating slurry. After sanding the surface coating slurry with a sand grinder, use a gravure coater to apply the surface coating slurry to both sides of the base film 7, and solidify it to obtain a diaphragm.
[0084] (4) Lithium-ion battery
[0085] The positive electrode, negative electrode and separator prepared above were assembled as follows:
[0086] After the positive electrode and the negative electrode are cut and sliced, the positive electrode, the separator, the negative electrode, and the separator are stacked in sequence and wound to obtain a battery cell. The battery cell is packaged, baked, injected, formed, sealed, sorted, and the open circuit voltage of the battery is tested to obtain a lithium-ion battery. The electrolyte is a commercially available conventional electrolyte containing lithium hexafluorophosphate (LiFP6).
[0087] In other embodiments, the component composition and thickness of the positive electrode active coating and the negative electrode active coating can be adjusted according to actual application requirements, or the type and thickness of the positive electrode current collector, the negative electrode current collector, and the base film 7 of the separator can be adjusted, or the type of electrolyte can be adjusted, provided that the normal use of the battery device is not affected.
[0088] Test Example 1
[0089] (1) 1C6V test:
[0090] The lithium-ion battery is charged at a constant current and constant voltage of 0.2C until the battery voltage reaches 4.45V. When the charging current decreases to 0.02C, the charging is stopped and left for 10 minutes. Then the lithium-ion battery is charged at a current of 1C until the battery voltage reaches 6V. The charging is stopped after 3 hours of continuous charging. The battery status is evaluated. If the battery does not catch fire or explode during the test, it is considered to have passed the 1C6V test. In order to ensure the accuracy of the data, 10 lithium-ion batteries of each type are prepared and tested independently, and the 1C6V overcharge pass rate is recorded.
[0091] 1C6V overcharge pass rate = number of batteries passing 1C6V test / total number of test samples × 100%.
[0092] (2) Capacity retention rate: The lithium-ion battery was charged at 0.2C constant current and constant voltage until the battery voltage reached 4.45V. When the charging current decreased to 0.02C, charging was stopped and the battery was left for 10 min. Then, it was discharged at 0.2C to 3.0V. The discharged capacity was recorded as the initial capacity. Then, the lithium-ion battery was charged at 0.7C at a temperature of 25±3℃. When the charging current decreased to 0.02C, charging was stopped. Then, it was discharged at 0.5C to 3.0V. This was used as a cycle to record the discharge capacity of the test object at the 400th cycle, and the capacity retention rate was recorded.
[0093] Capacity retention rate = discharge capacity at the 400th cycle / initial capacity × 100%.
[0094] Example 2
[0095] In order to further study the influence of the component content in the functional coating of the positive electrode, the corresponding positive electrode, separator, negative electrode and lithium ion battery were prepared according to the specific materials and amounts listed in Table 3 and the method and steps described in Example 1. The remaining raw material ratios and preparation methods were strictly consistent with those in Example 1. Then the test was carried out according to the method specified in Test Example 1. The final test results were averaged and shown in Table 4. For ease of comparison, the relevant information of the lithium ion battery of Example 1 is also included in the table below.
[0096] Table 3. Composition of functional coatings
[0097]
[0098] Table 4. Performance test results of lithium-ion batteries
[0099] Group 1C6V overcharge pass rate (%) 400 cycles capacity retention rate (%) Example 1 100% 96.8% Experimental Group 2-1 80% 96.5% Experimental group 2-2 80% 96.1% Experimental Group 2-3 100% 96.5% Experimental Groups 2-4 100% 96.0% Experimental Groups 2-5 100% 96.4% Experimental Groups 2-6 100% 96.1% Comparison group 2-1 50% 96.2% Comparison group 2-1 40% 96.4%
[0100] Result analysis:
[0101] By comparing the performance indicators of the above-mentioned experimental group and the comparative group, it can be found that the 1C6V overcharge pass rate of the lithium-ion batteries provided by Example 1 and experimental groups 2-1 to 2-6 is greater than 50%. Compared with the lithium-ion batteries provided by comparative groups 2-1 to 2-2, the lithium-ion batteries provided by Example 1 and experimental groups 2-1 to 2-6 have better overcharge resistance and flame retardant properties.
[0102] By comparing Example 1 with the lithium-ion batteries provided by Experimental Groups 2-1 and 2-2, it can be found that compared with the lithium-ion batteries of Experimental Group 2-1 in which the functional coating only uses metal oxide A and the lithium-ion batteries of Experimental Group 2-2 in which the functional coating only uses metal oxide B, the functional coating of the lithium-ion battery provided in Example 1 uses both metal oxide A and metal oxide B, and the 1C6V overcharge pass rate of the lithium-ion battery provided in Example 1 is greater than 80%, and the 400-cycle capacity retention rate is greater than 96.5%. This shows that the combination of metal oxide A and metal oxide B is beneficial to improving the structural stability and cycle stability of the lithium-ion battery, and can also improve the safety performance of the lithium-ion battery.
[0103] Example 3
[0104] In order to further study the influence of the component content in the surface coating of the separator, the corresponding positive electrode, separator, negative electrode and lithium ion battery were prepared according to the specific materials and amounts listed in Table 5 and the method and steps described in Example 1. The remaining raw material ratios and preparation methods were strictly consistent with those in Example 1. Then the test was carried out according to the method specified in Test Example 1. The final test results were averaged and shown in Table 6. For ease of comparison, the relevant information of the lithium ion battery of Example 1 is also included in the table below.
[0105] Table 5. Composition of surface coating
[0106]
[0107] Table 6. Performance test results of lithium-ion batteries
[0108]
[0109]
[0110] Result analysis:
[0111] By comparing the performance indicators of the above-mentioned experimental group and the comparative group, it can be found that the 1C6V overcharge pass rate of the lithium-ion batteries provided by Example 1 and experimental groups 3-1 to 3-3 is greater than 50%. Compared with the lithium-ion batteries provided by comparative groups 3-1 to 3-3 whose surface coatings of the diaphragms do not contain sodium fast ion conductors, the lithium-ion batteries provided by Example 1 and experimental groups 3-1 to 3-3 have better overcharge resistance and flame retardant properties.
[0112] By comparing Example 1 with the lithium-ion battery provided by Experimental Group 3-1, it can be found that when the surface coating uses sodium fast ion conductors, boron and / or phosphorus compounds at the same time, the overcharge resistance and cycle stability of the lithium-ion battery can be improved at the same time.
[0113] Further, by comparing the lithium ion batteries provided by Example 1, Experimental Group 3-2 to Experimental Group 3-3 with Comparative Group 3-1 to Comparative Group 3-3, it can be found that when the surface coating does not contain a sodium fast ion conductor, the lithium ion batteries with surface coatings containing ammonium borate or ammonium polyphosphate in Comparative Group 3-2 and Comparative Group 3-3 have higher overcharge resistance than the lithium ion batteries with surface coatings containing zinc borate in Comparative Group 3-1, but the cycle stability of the battery in Comparative Group 3-1 is slightly better than that of the batteries in Comparative Group 3-2 and Comparative Group 3-3. However, when the surface coating contains a sodium fast ion conductor, the lithium ion battery with surface coating containing zinc borate in Example 1 has a higher 1C6V overcharge pass rate and a higher 400-cycle capacity retention rate than the lithium ion batteries with surface coatings containing ammonium borate or ammonium polyphosphate in Experimental Group 3-2 to Experimental Group 3-3, that is, under the premise that the surface coating contains a sodium fast ion conductor, the lithium ion battery with surface coating containing zinc borate has better overcharge resistance and cycle stability.
[0114] Example 4
[0115] In order to further study the structure of the positive electrode and the separator and the influence of the thickness of the functional coating and the surface coating, the corresponding positive electrode, separator, negative electrode and lithium ion battery were prepared according to the specific materials and amounts listed in Table 7 and the method and steps described in Example 1. The remaining raw material ratios and preparation methods were strictly consistent with those in Example 1. Then the test was carried out according to the method specified in Test Example 1. The final test results were averaged and shown in Table 8. For ease of comparison, the relevant information of the lithium ion battery of Example 1 is also included in the table below.
[0116] Table 7. Structure of positive electrode and separator and thickness of functional coating and surface coating
[0117]
[0118] Note: "Contains 2 functional coating layers" in the column where "Positive electrode structure" is located means that in the experimental group / comparative group, the positive electrode includes the first positive electrode active coating layer 1, the first functional coating layer 2, the positive electrode current collector 3, the second functional coating layer 4, and the second positive electrode active coating layer 5, which are compounded in sequence. "Contains 1 functional coating layer" in the column where "Positive electrode structure" is located means that in the experimental group / comparative group, the positive electrode is composed of the first positive electrode active coating layer 1, the first functional coating layer 2, the positive electrode current collector 3, and the second positive electrode active coating layer 5, which are compounded in sequence. "No functional coating layer" in the column where "Positive electrode structure" is located means that in the experimental group / comparative group, the positive electrode is composed of the first positive electrode active coating layer 1, the positive electrode current collector 3, and the second positive electrode active coating layer 5, which are compounded in sequence.
[0119] The statement "with surface coating" in the column where "diaphragm structure" is located indicates that in the experimental group / comparative group, the diaphragm includes a first surface coating 6, a base film 7, and a second surface coating 8 arranged in sequence. The statement "without surface coating" in the column where "diaphragm structure" is located indicates that in the comparative group, the diaphragm is composed of a base film 7.
[0120] Table 8. Performance test results of lithium-ion batteries
[0121] Group 1C6V overcharge pass rate (%) 400 cycles capacity retention rate (%) Experimental Group 4-1 60% 97.7% Experimental Group 4-2 80% 97.5% Example 1 100% 96.8% Experimental Group 4-3 100% 95.2% Experimental group 4-4 80% 97.1% Experimental Group 4-5 100% 95.7% Experimental Groups 4-6 100% 95.1% Experimental Groups 4-7 60% 96.9% Comparison group 4-1 0% 97.9% Comparison group 4-2 50% 97.0% Comparison group 4-3 20% 97.5%
[0122] Result analysis:
[0123] By comparing the performance indicators of the above-mentioned experimental group and the comparative group, it can be found that the 1C6V overcharge pass rate of the lithium-ion batteries provided by Example 1 and experimental groups 4-1 to 4-7 is greater than 50%. Compared with the lithium-ion batteries provided by comparative groups 4-1 to 4-3 whose surface coatings of the diaphragms do not contain sodium fast ion conductors, the lithium-ion batteries provided by Example 1 and experimental groups 4-1 to 4-7 have better overcharge resistance and flame retardant properties.
[0124] By comparing the lithium-ion batteries provided in Example 1, experimental groups 4-7, and comparative group 4-3, it can be found that as the number of layers of the functional coating in the positive electrode structure increases, the 1C6V overcharge pass rate of the lithium-ion battery tends to increase, and the 400-cycle capacity retention rate of the lithium-ion battery tends to decrease. In Example 1, the positive electrode structure contains 2 layers of functional coating, the 1C6V overcharge pass rate is 100%, and the 400-cycle capacity retention rate reaches 96.8%.
[0125] By comparing the lithium-ion batteries provided by Example 1 and comparison groups 4-2 and 4-3, it can be found that the 1C6V overcharge pass rate measured in Example 1 is greater than the sum of the 1C6V overcharge pass rate of comparison group 4-2 and the 1C6V overcharge pass rate of comparison group 4-3. That is to say, by providing a functional coating on the positive electrode of the lithium-ion battery and providing a surface coating on the diaphragm, the flame retardant performance of the battery can be improved and the probability of thermal runaway of the battery due to overcharging can be reduced.
[0126] Comparing Example 1 with the lithium-ion batteries provided by Experimental Groups 4-1 to 4-3, it can be found that as the single-sided thickness of the functional coating in the positive electrode structure increases, the 1C6V overcharge pass rate of the lithium-ion battery tends to increase, and the 400-cycle capacity retention rate of the lithium-ion battery tends to decrease. When the single-sided thickness of the functional coating reaches 3 μm, the 1C6V overcharge pass rate reaches 100%. Comparing Example 1 with the lithium-ion batteries provided by Experimental Groups 4-4 to 4-6, it can be found that as the single-sided thickness of the surface coating in the diaphragm structure increases, the 1C6V overcharge pass rate of the lithium-ion battery tends to increase, and the 400-cycle capacity retention rate of the lithium-ion battery tends to decrease. When the single-sided thickness of the surface coating reaches 1 μm, the 1C6V overcharge pass rate reaches 100%.
[0127] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium ion battery, characterized in that: It includes a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode; The positive electrode comprises a positive electrode active coating, a functional coating and a current collector, wherein the positive electrode active coating is connected to the current collector through the functional coating, the functional coating comprises vinyl chloride-acrylate resin, water-based acrylic resin and metal oxide, and the metal oxide comprises at least one of aluminum oxide, zirconium oxide, zinc oxide, magnesium oxide and lithium oxide; The separator includes a base membrane and a surface coating, wherein the surface coating includes a sodium fast ion conductor.
2. The lithium-ion battery according to claim 1, characterized in that: The proportion of chlorine in the functional coating is 2.2-13.6 wt %.
3. The lithium ion battery according to claim 1, characterized in that: In the functional coating, the metal oxide includes metal oxide A and metal oxide B, the metal oxide A includes at least one of aluminum oxide, zirconium oxide, zinc oxide, and magnesium oxide, and the metal oxide B includes lithium oxide.
4. The lithium ion battery according to claim 3, characterized in that: In the functional coating, the mass ratio of the metal oxide A to the metal oxide B is 1-20:1-20.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: In the positive electrode, the thickness of the functional coating layer is 1 to 5 μm.
6. The lithium ion battery according to claim 1, wherein: In the separator, the surface coating further comprises a boron compound and / or a phosphorus compound.
7. The lithium ion battery according to claim 6, characterized in that: In the separator, the surface coating further includes zinc borate.
8. The lithium ion battery according to claim 6, characterized in that: In the raw materials used to prepare the surface coating, the sum of the masses of the boron compound and the phosphorus compound accounts for 1 to 10 wt %.
9. The lithium ion battery according to any one of claims 1 to 4 and 6 to 8, characterized in that: The thickness of the surface coating is 0.5-3 μm.
10. The lithium ion battery according to claim 1, characterized in that: The positive electrode active coating layer of the positive electrode faces the separator.
11. A method for preparing a lithium ion battery according to any one of claims 1 to 10, characterized in that: The following operations are included: a. Preparing a positive electrode: applying a functional coating slurry for preparing a functional coating on both sides of a current collector, curing, and obtaining a composite layer containing the functional coating and the current collector, wherein the functional coating slurry comprises vinyl chloride-acrylate resin, water-based acrylic resin, metal oxide, and solvent; then applying a positive electrode active slurry for preparing a positive electrode active coating on both sides of the composite layer, curing, and obtaining the positive electrode; b. Preparation of the diaphragm: applying the surface coating slurry for preparing the surface coating to at least one side of the base film and curing the slurry to obtain the diaphragm.
Citation Information
Patent Citations
Quickly-chargeable / dischargeable lithium ion battery and manufacture method thereof
CN105406083A
A cathode current collector water-based protective coating
CN109273722A
Preparation method of high-strength and high-energy-density LATP composite film
CN113067098A
Lithium ion battery, lithium ion battery positive plate and preparation method of lithium ion battery positive plate
CN114373887A
Secondary battery and electric device
CN116404275A